The maximum debit acid stimulus Histalog comparison using the Maximum Debit Histalog acid and insulin as stimulants - Chahud Isee, Alfredo (1967)
The authors study the gastric secretion using a quadruple dose Histalog two objects : first, to determine the Maximum Debit acid ie the maximum gastric secretion and second , to compare the stimulating effect of Histalog with the insulin hypoglycemia for which use two series of patients : the first , made up of 170 persons ( 30 normal , 30 with gastric ulcer, duodenal ulcer 71 , 30 with atrophic gastritis and gastritis surface 9 ) , and in which the maximum is determined gastric secretion in the period of 30 '- 90' of stimulation ; The second set consisting of 80 individuals (7 normal , 20 gastric ulcer , duodenal ulcer 40 and 13 carriers of atrophic gastritis ) , which determine the gastric secretion is stimulated by higher than Histalog stimulated insulin hypoglycemia. Conclude by discussing the likely mechanism of action of Histalog and hypoglycemic action of insulin and insulin itself on gastric secretion inhibition as a factor of gastric secretion may explain the difference of values ​​that are .